PENDETEKSIA KECURANGAN (FRAUD) YANG DIPENGARUHI OLEH INDEPENDENSI DAN KOMPETENSI AUDITOR INTERNAL (Studi Kasus Pada Inspektorat Wilayah II Kementerian Agama Republik Indonesia) - Rahmanda, Fatma; Yuniarti, Rita (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2019)
This study aims to determine the effect of independence and competence of internal auditors on the detection of fraud in the Inspectorate Region II of the Indonesian Ministry of Religion. The research method used was explanatory. The population in this study were all auditors working at the Inspectorate of Region II of the Indonesian Ministry of Religion. The results of this study indicate that the independence and competence of internal auditors influence the detection of fraud in the Inspectorate of Region II of the Indonesian Ministry of Religion. Keywords : Competence, Fraud detection, and Independence.